Telemedicine Based on Healthcare System - Ghosh, Tania; Bhowmik, B.B (International Journal of Computer Sciences and Engineering, 2018)
Telemedicine is the process that allows the professionals of the healthcare to assess, diagnose and to treat the patients with the help of modern technology i.e., telecommunication technology even from a long distance. In this paper some of the topics of last 40years has been discussed i.e. where the work of Telemedicine has been held, what advantages it provided to the health care system, what was the main use of those advantages and so on. Thus from our study we get to know that the fundamental of Telemedicine is mainly to transfer the medical data, and for that purpose several telecommunication technologies such as Radio frequency communication, satellite communication, are used. The main use of telemedicine can be seen in rural sphere. Thus day by day the technology of Telemedicine has provided many facilities to the health care system and has increased patient’s satisfaction level to its top and hopefully will provide a lot of amazing features in the future.